Fostering Creative Competencies in Visual Arts for 5th–7th Grade Students: Innovative Approaches - Tog‘aev Keldiyor Xamidovich (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article investigates innovative approaches to fostering creative competencies in visual arts lessons for students in grades 5–7. Emphasis is placed on developing students’ imagination, critical thinking, and visual problem-solving skills through interactive learning, collaborative projects, and diverse artistic techniques. The study highlights practical strategies that teachers can implement to enhance creativity and engagement in the classroom, promoting both personal and cognitive development.